If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 21 + 6 = s Combine like terms: 21 + 6 = 27 27 = s Solving 27 = s Solving for variable 's'. Move all terms containing s to the left, all other terms to the right. Add '-1s' to each side of the equation. 27 + -1s = s + -1s Combine like terms: s + -1s = 0 27 + -1s = 0 Add '-27' to each side of the equation. 27 + -27 + -1s = 0 + -27 Combine like terms: 27 + -27 = 0 0 + -1s = 0 + -27 -1s = 0 + -27 Combine like terms: 0 + -27 = -27 -1s = -27 Divide each side by '-1'. s = 27 Simplifying s = 27
| 5f+23=28 | | 12n+2-5= | | 9x^5-12x^4+6x+5=0 | | 118/x=20 | | 3x^2+0x+1=0 | | 4y-13=35 | | -1(x-7)+15x= | | 24/y=(1-(0.95x/x)) | | X/12=36/6 | | 3x^2+4y-180=0 | | 24/18= | | 32.8=3.5b | | -6=v/18= | | x-7/64/3 | | (x-1)*(x+3)=0 | | -108/18= | | 56.52=2*3.14*r | | ln(6x-8)=1.3 | | 7a+3=66 | | 10+10x=109+1x | | 6(n+7)=60 | | ((-18x^(0)a^(3))/(6(x^(-2))(x^(3)a^(2))))^(2) | | =80 | | 9(-3+p)=-54 | | 9x+8x-3x-5=23 | | 5(b-5)=70 | | 2+7x=56+1x | | 6=-8y+3(y-3) | | 0.5x+0.2x=0.4x+5 | | 179=5d/11 | | 7y+3y-10=180 | | -6+8a+4x-2+2a=10a+4 |